Badminton Learning for Students with Intellectual Disabilities at Special Needs School - Antika Pramesti Maharani Putri; Erick Burhaein (Jurnal Pendidikan Jasmani (JPJ), 2026)
This study aims to describe the implementation of badminton learning for students with intellectual disabilities at the Mandiraja State Special Needs School in Banjarnegara, Jawa Tengah. The study used a qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The research subjects included physical education teachers and students with intellectual disabilities. The results showed that badminton learning still faces several obstacles, especially in adjusting learning objectives, implementing activities, modifying learning, and evaluating learning outcomes. Differences in students' motor and cognitive abilities are the main factors that influence the learning process. Nevertheless, teachers have implemented adapted learning strategies through simplifying materials, modifying equipment and game rules, and evaluating according to individual student abilities. Adapted designed badminton learning can support student engagement and help develop motor skills gradually.